The First Case Report in Italy of Di George Syndrome Detected by Noninvasive Prenatal Testing - Giuseppina Rapacchia; Cristina Lapucci; Maria Carla Pittalis; Aly Youssef; Antonio Farina (Case Reports in Obstetrics and Gynecology)
Panorama Plus (Natera), a single-nucleotide polymorphism- (SNP-) based approach that relies on the identification of maternal and fetal allele distributions, allows the detection of common aneuploidies and also incorporates a panel of 5 microdeletions including Di George syndrome. We report here the first case of Di George syndrome detected by NIPT in Italy; blood was drawn at 12 weeks’ gestation. The patient had an amniocentesis to confirm the diagnosis by MLPA (multiplex ligation-dependent probe amplification) and an ultrasound aimed to detect the features associated with the syndrome. A right aortic arch and suspect of thymus atrophy were detected, but not other severe malformations typical of the disease. The patient terminated the pregnancy at 17 weeks. NIPT allowed an early screening of Di George syndrome. As the patient was at low risk, it is likely that an ultrasound would have missed the condition.